2023
DOI: 10.1002/chem.202203827
|View full text |Cite
|
Sign up to set email alerts
|

Chiral and Structural Polymorphism of Fibril Architectures of Homologous Lysozymes

Abstract: Amyloid fibrils are fascinating and complex structures with the multilayered chiral organization. Using the multimodal methodology, including VCD, ECD, cryo‐EM, and TEM, we characterized in detail different levels of organization (secondary structure/protofilament/mesoscopic structure) of amyloid fibrils prepared from proteins highly homologous in the structure (hen egg white and human lysozymes). Our results demonstrate that small changes in the native protein structure or preparation conditions translate int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…1). [42][43][44][45][46][47][48] Due to the 'superchiral' long-range organization of the amyloid fibrils, they provide a very intense chiroptical readout. The enhanced VCD is observed not only for fibrils formed from proteins, but also for short peptides forming long, multistrand and twisted fibrillary architectures.…”
Section: Biomacromolecules and Biogenic Supramoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [42][43][44][45][46][47][48] Due to the 'superchiral' long-range organization of the amyloid fibrils, they provide a very intense chiroptical readout. The enhanced VCD is observed not only for fibrils formed from proteins, but also for short peptides forming long, multistrand and twisted fibrillary architectures.…”
Section: Biomacromolecules and Biogenic Supramoleculesmentioning
confidence: 99%
“…The most characteristic VCD signal of amyloid fibrils is the amide I band, derived from the excitonically coupled CQO stretching vibrations. Several studies 43,44,46,52,53 have demonstrated that the sign of this coupled might be positive or negative and that some factors, such as pH, 52 a solvent 53 or agitation, 43 can reverse it. Currently, it is assumed that the sign of the amide I VCD couplet is associated with the protofilament twist, 46 making VCD a rather unique method providing information about the protofilament handedness, hence constituting an important complement to other chiroptical and microscopic techniques in the characterization of amyloid fibrils (Fig.…”
Section: Biomacromolecules and Biogenic Supramoleculesmentioning
confidence: 99%
“…For all three proteins, significant enhancement of VCD was previously reported. 3,7 We decided to explore and directly compare the ROA with VCD, electron circular dichroism (ECD) and transmission electron microscopy (TEM) data to control and characterize the amyloid fibril formation. The experimental details are given in the ESI; † briefly, the fibrils were prepared under the previously reported conditions, i.e., at pH of 2.0 and at the elevated temperature of 60 1C.…”
mentioning
confidence: 99%
“…The experimental details are given in the ESI; † briefly, the fibrils were prepared under the previously reported conditions, i.e., at pH of 2.0 and at the elevated temperature of 60 1C. 3,7 The lysozyme fibrils were obtained using agitation at 1400 rpm, resulting in the formation of thicker (HEWL, HL) and shorter (HEWL) fibrils compared with non-agitated samples, 7 presumably increasing the signal intensity and minimizing the anisotropy that could lead to artifacts in the ROA spectra. For both homologous lysozymes, ROA was measured at various time points from the onset of protein fibrilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation